Impact of 14-day bed rest on serum adipokines and low-grade inflammation in younger and older adults - Jurdana, Mihaela (Age (Dordr), 2015)
Ageing and inactivity both contribute to systemic inflammation, but the effects of inactivity on inflammation in healthy elderly individuals have not been elucidated. We hypothesised that 14-day bed rest could affect the pro- and anti-inflammatory markers in young subjects differently than in older adults. A short-term 14-day horizontal bed rest study (BR14) has been used as a model of inactivity in two groups of healthy male volunteers: 7 aged 18–30 years (young) and 16 aged 55–65 years (older adults). The effects of inactivity on inflammation were compared. Key low-grade inflammation mediators, tumour necrosis factor α (TNF-α), interleukin-6 (IL-6), visfatin, resistin, and anti-inflammatory adiponectin were measured in fasting serum samples, collected at baseline (BDC) and post BR14. Young responded to BR14 by increasing serum visfatin and resistin while older adults responded to BR14 by increasing IL-6 and TNF-α. In addition, serum adiponectin increased in all participants. Data from correlation analysis demonstrated positive association between Δ serum visfatin and Δ IL-6 in both groups, while Δ serum adiponectin was negatively associated with Δ TNF-α in young and positively associated with Δ resistin in the older adults. As little as 14 days of complete physical inactivity (BR14) negatively affected markers of low-grade inflammation in both groups, but the inflammation after BR14 was more pronounced in older adults. The effect of BR14 on IL-6 and resistin differed between young and older adults. Inflammatory responses to BR14 in older adults differed from those reported in the literature for obese or subjects in pathological states, suggesting potentially different mechanisms between inactivity- and obesity-induced inflammations.